# Let A=\begin{bmatrix}4 & 0 &5 \\-1 & 3 & 2

Let $$A=\begin{bmatrix}4 & 0 &5 \\-1 & 3 & 2 \end{bmatrix}$$,
$$B=\begin{bmatrix}1 & 1 &1 \\3 & 5 & 7 \end{bmatrix}$$,
$$C=\begin{bmatrix}2 & -3 \\0 & 1 \end{bmatrix}$$
Find: $$\displaystyle{3}{A}-{B}$$, and $$\displaystyle{C}\times{B}+{A}$$

• Questions are typically answered in as fast as 30 minutes

### Plainmath recommends

• Get a detailed answer even on the hardest topics.
• Ask an expert for a step-by-step guidance to learn to do it yourself.

$$A=\begin{bmatrix}4 & 0 &5 \\-1 & 3 & 2 \end{bmatrix}$$
$$B=\begin{bmatrix}1 & 1 &1 \\3 & 5 & 7 \end{bmatrix}$$
$$C=\begin{bmatrix}2 & -3 \\0 & 1 \end{bmatrix}$$
$$(3A-B)=\begin{bmatrix}4 & 0 &5 \\-1 & 3 & 2 \end{bmatrix}-\begin{bmatrix}1 & 1 &1 \\3 & 5 & 7 \end{bmatrix}$$
$$B=\begin{bmatrix}12 & 0 &15 \\-3 & 9 & 6 \end{bmatrix}-\begin{bmatrix}1 & 1 &1 \\3 & 5 & 7 \end{bmatrix}$$
$$(3A-B)=\begin{bmatrix}11 & -1 &14 \\-6 & 4 & 1 \end{bmatrix}$$
$$C\times=\begin{bmatrix}2 & -3 \\0 & 1 \end{bmatrix}^t=\begin{bmatrix}2 & 0 \\-3 & 1 \end{bmatrix}$$
$$C\times B=\begin{bmatrix}2 & 0 \\-3 & 1 \end{bmatrix}\begin{bmatrix}1 & 1 &1 \\3 & 5 & 7 \end{bmatrix}$$
$$=\begin{bmatrix}2 & 2 &2 \\0 & 2 & 4 \end{bmatrix}$$
$$C\times B+A=\begin{bmatrix}2 & 2 &2 \\0 & 2 & 4 \end{bmatrix}+\begin{bmatrix}4 & 0 &5 \\-1 & 3 & 2 \end{bmatrix}$$
$$=\begin{bmatrix}6 & 2 &7 \\-1 & 5 & 6 \end{bmatrix}$$